Pembatalan Pernikahan dalam Perspektif Islam dan Kristen - Siregar, Evi Yulianti; Harahap, Indra; Syahrin, Abu (Lembaga Yasin AlSys, 2023)
This research is entitled Annulment of Marriage in Islamic and Christian Perspectives. If the conditions for a husband to have more than one wife are not fulfilled, then a new marriage can be annulled by the Court whose jurisdiction includes the place where the marriage took place or the place of residence of both husband and wife, where the husband or wife and still have another relationship with her lover. The occurrence of annulment of marriage is not only in Islam but also in Christianity. Things that cause the cancellation of forced marriages, polygamy, during the iddah period, infidelity, different religions and so on. The research method used by researchers is a qualitative research method with a library research model. In this study the authors use the historical approach to the historical method while the theoretical approach is comparative theory. Data sources in this study are divided into primary sources and secondary sources. The results and findings of this study are; 1) The Paradigm of the Cancellation of Marriage Humans are multidimensional and complex creatures of God. Since the history of human civilization was written, it has always been used as an object of study that never ends for study. 2) The Islamic view of annulment of marriage. An annulment of marriage in Islam is said to be a marriage in which there is damage in the marriage and it is permissible to break up or destroy the marriage. 3) The Christian View of Annulment of Marriage. An annulment of marriage in Christianity is an invalid marriage because he is still bound by one of the two parties or there is still a relationship and on the basis that the marriage is still there.